DESIGNING BUSINESS MODEL CANVAS TRANSFORMS INTO BALANCED SCORECARD IN THE XYZ UNIVERSITY IN INDONESIA - Mia Agusty, Rosana (Dinasti International Journal of Management Science, 2020)
Business Model Canvas becomes a company performance appraisal. BMC is widely used for initial design of business process. In this research, the author is focusing on analyzing business process in XYZ University, one of the largest well known universities in Indonesia. Through the business process, translated onto BMC to see wider view from the beginning to the end of the process. The BMC and then transforms into 4 areas of Balanced Scorecard to see percentage of 4 areas of the business process. Type of data is primary, by observing and interviewing some employees, students, and alumni, and secondary by searching information through social media. The methods is Business Model Canvas and Balanced Scorecard. The result is by including some inputs, business process of XYZ University confirms that the university will survive in long term and has good capacity to remain as one of the high rank universities in Indonesia.